Reactions of titanium imides and hydrazides with boranes - Mellino, S; Stevenson, L; Clot, E; Mountford, P (American Chemical Society, 2017)
We report the first reactions of titanium imido, alkylidene hydrazido and dimethylhydrazido compounds with the boranes H2BTex, 9-BBN, HBArF2 and HBPin (Tex = tert-hexyl; ArF = C6F5). Reactions of Cp*Ti{MeC(NiPr)2}(NTol) with H2BTex, 9-BBN or HBArF2 resulted in the hydride-bridged adducts Cp*Ti{MeC(NiPr2)2}{N(Tol)HBRR′} without B–H bond cleavage. Cp*Ti{MeC(NiPr)2}(NNCPh2) (4) reacted with HBArF2 via a sequence of steps involving adducts at the - and then nitrogen of the NNCPh2 ligand, before slow 1,2-addition of B–H across the N=CPh2 double bond of 4 forming Cp*Ti{MeC(NiPr)2}{NN(BArF2)CHPh2} (17). The other boranes reacted immediately with 4 to form homologues of 17. These products are the first examples of borylhydrazido(2-) complexes. Reaction of Cp*Ti{MeC(NiPr2)2}(NNMe2) (2) with HBArF2 gave the hydride-bridged adduct Cp*Ti{MeC(NiPr2)2}{N(NMe2)HBArF2}, whereas with HBPin B–H bond cleavage occurred to form the borylhydrazide(1-)-hydride Cp*Ti{MeC(NiPr)2}(H){N(BPin)NMe2}. Finally, reaction of 2 with 9-BBN dimer resulted in H2 elimination and formation of Me2NBC8H14 and Cp*Ti{MeC(NiPr)2}(NBC8H14), a rare of example of a borylimido compound.